Reflective Thinking Profile of High School Students in Solving Hots-Type Questions Reviewed from Adversity Quotient - Sumardi, Sumardi; Tyas, Anggit Cahyaning (Universitas Muhammadiyah Mataram, 2022)
The many Adversity Quotient kinds that each individual possesses will have an impact on how they respond to addressing difficulties. The person's efforts to tackle the current difficulties get more difficult as their degree of Adversity Quotient rises.This study's purpose is to describe students' reflective thinking profile in solving HOTS-type questions in terms of level adversity quotient. The subjects of this study, namely three students from class X of senior high school, were taken based on the Adversity Responses Profile (ARP) questionnaire results. The data collection techniques carried out by this study include analysis of test answer results and in-depth interviews. In addition, source triangulation is used for the validity of the data. Data analysis is carried out through five stages: data collection, data reduction, data presentation, data verification, and conclusions. The data table is obtained from the results of the analysis of the answers to the three questions presented in the form of tables based on the components of reflective thinking and problem-solving steps. The research results in this article are three, (1) the reflective thinking profile of students in solving HOTS-type questions can meet the components of reflective thinking and go through the steps of problem-solving Polya: analysis, plan, implement, and evaluation; (2) the reflective thinking profile of students in solving HOTS-type questions cannot meet all the components of reflective thinking, namely the comparing component and through the steps of problem-solving Polya: analysis, plan, implementation, and evaluation. However, at the step of the problem-solving plan, there is one plan that is not by mathematical concepts; and (3) the reflective thinking profile of quitter students in solving HOTS-type problems cannot meet all the components of reflective thinking, namely the contemplating component and not going through all the steps of problem-solving, namely the step of implementing the plan and evaluation. The three types of adversity questions have different reflective thinking profiles according to the criteria of each type.